On the vortical behaviour of annular impinging jets - Zhou, Ran (2017)
This study aims to examine and analyse the vortical behaviour of annular impinging jets upon convex cylindrical surfaces with diameter D = 20, 40 and 80 mm. Laser Induced Fluorescence (LIF) as well as Digital Particle Image Velocimetry (DPIV) experiments are performed at Reynolds number Re=370 with nozzle-to-cylinder separation distance of H = 20, 40 and 80 mm, while both scenarios along cylinder straight edges and curvature surfaces are studied. Observations are made on vortex shape, movement and location via LIF as well as DPIV results to conclude on vortical behaviours and flow dynamics. In depths comparison is done between flow pattern of different experiment configuration to determine the effect of various setup parameters. These behaviours are also compared with those of similar existing researches and possible explanation will be presented in this report.